The Potential of Organic Mungbean Production Under Phon Phisai - Sriphadet , Sukumaporn (YRU Journal of Science and Technology, 2021)
Mungbeans are necessary in the organic farming system because mungbeans are able to fixed nitrogen and fertilized to the soil. Moreover, the demand for mungbeans is high but the production is not enough to meet the demand. Therefore, this research was focused on studying the potential of mungbean seed production under the Phon Phisai soil series in 16 varieties at Chiang Khruea Sub-district, Mueang District, Sakon Nakhon Province during September to December 2019. The experimental design was randomized complete block design (RCBD) with 5 replications. The data collections on day to harvest, plant height, number of pods per plant, number of seeds per pod, 100 seed weight and total yield were investigated. The results showed significant differences among characters. Uthong2 has the highest harvesting days and number of pods per plant. CN36 showed the highest plant height. KUML1 showed the highest number of seeds per pod. KUML3 showed the highest pod length. KUML4 were the highest in 100 seed weight. While, CN2 has the highest yield per rai. When analyzing the correlation, it was found that yield was positively correlated with plant height, number of pods per plant and 100 seed weight, but negatively correlated with harvesting day.